Acupuncture induced pneumothorax: A case report - Ninadini Shrestha (Clinical Case Reports, 2020)
Abstract Various forms of alternative medicinal practices are gaining popularity. With this, there will be rise in the complications arising from these practices. Acupuncture is also such practice which though safe can rarely cause life‐threatening complications.